Therapeutic Management Of Anoestrus And Suboestrus Buffaloes Under Field Conditions Using Hormonal And Non-Hormonal Remedials - Butani, M.G.; Dhami, A.J.; Sarvaiya, N.P.; Shah, R.G.; Killedar , Ankita (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
The present study was carried out during breeding season on 98 anoestrus / suboestrus buffaloes to evaluate therapeutic efficacy of various hormonal and non-hormonal drugs in inducing oestrus and conception. In all 37 and 29 true anoestrus and 17 suboestrus buffaloes were treated with Tono-Prepaline-Cyclomin-Lugols (Inj. Protone 10 ml + Inj. Vitamin-A 6 ml, 4 times each at 4-5 days interval, Cyclomin-7 bolus orally every 3rd day, and 0.5 % Lugol’s iodine solution 10 ml i/ut or on os once), GnRH (Receptal 5.0 ml i/m once) and PGF2α (Juramate 2.0 ml i/m once), respectively, keeping 15 animals as untreated control. Animals detected in oestrus were inseminated by the trained lay inseminators. The oestrus induction response with PGF2α was the highest (100 %), followed by GnRH (89.66 %) and Tono-Prepaline-Cyclomin group (83.78 %), with the corresponding oestrus induction intervals of 3.59±0.44, 20.73±3.29 and 28.03±3.23 days, and conception rates at induced oestrus of 35.29, 26.92 and 38.71 %, respectively. The overall conception rates of 3 cycles for the three protocols were almost identical (76.47, 73.03 and 74.19 %), but with significantly (P
Keywords: Anoestrus; Buffaloes; Hormonal/Non-hormonal therapy; Oestrus induction; Conception